2000
DOI: 10.1046/j.1365-2842.2000.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characteristics of hypernasality in maxillectomy patients 1

Abstract: To reveal the acoustic characteristics associated with hypernasality and to ascertain their correlation to the severity of hypernasality, 30 speech samples produced by 15 maxillectomy patients were acoustically analysed with and without an obturator prosthesis in place. The isolated, sustained Japanese vowel /i/ was used as the stimulus for acoustic measurement and perceptual judgment to evaluate the severity of hypernasality. Normalized 1/3-octave spectral analysis demonstrated the spectral characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 14 publications
3
40
0
2
Order By: Relevance
“…Difficulty with production of /k/ originates from velar function difficulties. The decreased size of the vowel triangle of patients was mainly caused by deviant formant values of /i/ and is in accordance with earlier studies [13,14,19] . Inadequate movement of the tongue regarding height (F1) and anterior-posterior movement (F2) may result in distorted vowels.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Difficulty with production of /k/ originates from velar function difficulties. The decreased size of the vowel triangle of patients was mainly caused by deviant formant values of /i/ and is in accordance with earlier studies [13,14,19] . Inadequate movement of the tongue regarding height (F1) and anterior-posterior movement (F2) may result in distorted vowels.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the vowel /i/ itself also proved to predict subjective evaluations: patients had a higher F1 and a lower F2. These results are in agreement with the results of earlier research on pathological speech [14,19] (both concerned maxillectomy patients), but are not in agreement with results on research concerning partial glossectomy, where it was found that only gender and complication after surgery were of influence on altered F1 values [22] .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In terms of nasality (i.e., resonance), one-third octave spectral analysis was employed as a means of gauging these differences and their relationship to expressions of sarcasm. This form of analysis, which is performed by applying a onethird octave filter to the important frequencies of a steady state portion of a vowel and measuring the resulting values, is known to correlate well with expert ratings of the presence and degree of clinical hypernasality regardless of etiology, patient age (pediatric or adult) or gender, and across languages (Kataoka et al, 1996(Kataoka et al, , 2001aLee et al, 2003Lee et al, , 2004Yoshida et al, 2000). These additional acoustic measures allow the present literature on sarcasm to be extended in a meaningful way.…”
Section: The Present Studymentioning
confidence: 99%
“…1 Post-surgical maxillary defects result in difficulty in speech, impaired masticatory function & nasal regurgitation. 2,3,4 The primary goal of rehabilitating these defects include separation of oral & nasal cavities to allow adequate mastication, deglutination, articulation & the soft tissue support to restore acceptable esthetic to improve the quality of life of these individuals. 5 There are many methods for rehabilitate these defects, one of them is obturator prosthesis.…”
mentioning
confidence: 99%